Teaching for impact: exploring pedagogical approaches in sexuality education in South African rural schools - Adekola, Ayobami Precious (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
The effectiveness of sexuality education programmes depends on teachers' approaches to curriculum delivery. The effectiveness of sexuality education among school-going adolescents could be enhanced if teachers’ pedagogical approaches are understood and supported by all stakeholders. This study determined the approaches used for delivering sexuality education curricula at the selected rural schools from learners’ perspectives. Leveraging a phenomenological lens, this study explored rural learners' lived experiences of sexuality education programme in their schools located in King Cetshwayo district, South Africa. Focus group interviews were conducted in 2020 in nine rural high schools. Eighty-four learners were purposively sampled to participate in the study. Transcribed data from the focus group interviewsnwas analysed using the interpretative phenomenological analysis framework and the Information- Motivation-Behavioral Skills (IMB) model. Findings revealed two approaches used by educators to deliver sexuality education in the research setting, namely, structured and unstructured learning approaches. The study additionally highlighted areas of the curriculum covered by educators in these rural-based schools. I recommend rigorous and continuous training of teachers on sexuality education curriculum contents and pedagogy to enhance the effectiveness of curriculum implementation in the research setting.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 1, Volume 8, 2024
Keywords: Adolescent; Learner; Rural-based schools; Sexuality education; Teaching approaches; Rural children --South Africa.; Rural schools; Education -- Curricula; Curriculum based assessment; Sex instruction